Accuracy of steps measured by smartphones-based WeRun compared with ActiGraph-GT3X accelerometer in free-living conditions - Yao, Qinqin; Wang, Jing; Sun, Yucong; Zhang, Li; Sun, Shuangyuan; Cheng, Minna; Yang, Qinping; Wang, Siyuan; Huang, Ling; Lin, Tao; Jia, Yingnan (Frontiers in Public Health, 2022)
Objectives: The purpose of this study was to evaluate the accuracy and reliability of steps tracked by the smartphone-based WeChat app compared with the Actigraph-GT3X accelerometer in free-living conditions. Design: prospective cohort study Methods: A total of 103 employees in the Pudong New Area of Shanghai, China, participated in this study. The participants wore an ActiGraph-GT3X accelerometer at three time points from August 2019 to September 2019 (Time1), December 2019 (Time2) and September 2020 (Time3). Each time, they wore the accelerometer continuously for seven days. The ActiGraph-GT3X accelerometer was used to assess participants’ seven-day step counts. The smartphone-based WeChat step counts were collected in the corresponding period when subjects wore accelerometers. The subjects were invited to complete a basic demographic characteristics questionnaire and undergo physical examination to obtain health-related results such as height, body weight, body fat rate, waist circumference, hip circumference, and blood pressure. Results: Based on 103 participants’ 21 days of data, we found that the Spearman correlation coefficient between them was 0.725 (P < 0.01). The average number of WeChat steps measured by smartphones was 8,974 (4,203) per day, which was higher than those measured by accelerometers (8,462±3486 per day). Demographic characteristics and different conditions can affect the consistency of measurements. The consistency was higher in those who were male, older, master’s degree and above educated, and traveled by walking. Working days and August showed stronger correlation than other working conditions and time. The test-retest reliability coefficients of WeChat steps ranged from 0.392 to 0.646. A multiple regression analysis adjusted for age, gender, and MVPA/step counts measured during Time1 showed that body composition (body weight, BMI, body fat percentage, waist circumference, and hip circumference) was correlated with moderate-to-vigorous intensity physical activity, but there was no correlation with WeChat step counts. Conclusions: The smartphone-based WeChat app can be used to assess physical activity step counts and is a reliable tool for measuring steps in free-living conditions. However, WeChat step counts’ use is potentially limited in predicting health-related outcomes.